Economic analysis of knowledge: The history of thought and the central themes - Samuli Leppälä (Duke University, Center for the History of Political Economy (CHOPE), 2012)
Following the development of knowledge economies, there has been a rapid expansion of economic analysis of knowledge, both in the context of technological knowledge in particular and the decision theory in general. This paper surveys this literature by identifying the main themes and contributions and outlines the future prospects of the discipline. The wide scope of knowledge related questions in terms of applicability and alternative approaches has led to the fragmentation of research. Nevertheless, one can identify a continuing tradition which analyses various aspects of the generation, dissemination and use of knowledge in the economy.
Keywords: D80; O30; I20; B00; 330; knowledge; information; belief; uncertainty; innovation; intellectual property rights; scientific research; technological change